Limitations of Authority of Implementation of Tasks In Running The Local Government Duty - Susanto; Mega Lestari (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
Where constitutional conflicts occur, which is actually a law that prohibits Acting from signing APBD, but a Ministerial Regulation allows Plt to sign APBD. Where there are written rules that leave regulations outside the State Dependency for Governors, Regents and Mayors explaining an authority written by the Acting Minister of Domestic Affairs Article 9 Letter d paragraph 1 Number 74 Year 2016. That can be signed if obtained approval from the minister in writing which is about the Regional Budget and Regional Regulations on the Organization of Regional Apparatuses. However, there is a difference wherein that the Finance Law no 17 of 2003 is different from the Minister of Home Affairs Regulation 74 of 2016. Bring the contents of the Financial Act Number 17 of 2003 to state the written financial management authority that obtains power from the president, which is meant towards the regional head. Whereas where the Head of Province, regent, and mayor who are regional government officials can work on regional finances and represent regional officials in the ownership of separated regional assets. The contents are the rules written in article 6 letter c of Act 17 of 2003 concerning finance. Therefore, where the Permendagri's position is under the Act. If the APBD can be signed by an Acting Officer, then it can be sued and may be invalid. Where, there are provisions in the signing of the Regional Budget which is legitimate or is a Governor or Acting Actor, not an Acting Actor. Although where Permendagri Number 74 of 2016 can make APBD signed by the Acting Act, the financial law states that the Governor or Acting Actor can sign the APBD except Acting.